(untitled) (Eurasian Journal of Philology Science and Education, 2025)
This article provides a consistent analysis of psychologism in modern Kazakh short prose. Using the example of the stories by Gerold Belger, Nikolai Verevochkin, and Asel Omar, the forms of recreating psychologism in fiction are explored. The purpose of this study is to analyze various forms of psychologism in the works of modern kazakh short prose, taking into account their belonging to the method of realism. The main scientific idea of the study is that the various approaches of Kazakhstan writers to convincingly depict the inner world of literary heroes based on determinism show the diversity of psychological tools of modern literature. The scientific significance of the work is determined by the fact that its results and conclusions can serve to carry out an in-depth analysis of new artistic material. The practical significance of the work is expressed in the fact that its materials can be used as a basis for the development of classes on the study of psychology in modern kazakh prose. To achieve the purpose of the study, the following methods were used: descriptive, poetical-structural, comparative, historical-literary. In addition, the interpretation method was used to make sense of the material. The use of these methods ensured the reliability of the scientific results obtained. The article establishes that Kazakhstan authors use various forms of psychologism to realistically depict characters based on the implementation of the principle of determinism, which determines the connection between their inner world and behavior. Keywords: psychologism, determinism, kazakh literature, short story, realism.